Environmental effectiveness of GAEC cross-compliance Standard 3.1 Ploughing in good soil moisture conditions and economic evaluation of the competitiveness gap for farmers - Francaviglia, Rosa; Carroni, Antonio Melchiorre; Ruda, Paola; Salis, Mauro; Bazzoffi, Paolo; Carnevale, Silvia; Rocchini, Andrea; Troccoli, Antonio; Russo, Mario; Speroni, Marisanna; Borrelli, Lamberto; Cabassi, Giovanni; et al. (Italian Journal of Agronomy, 2015)
Within the MO.NA.CO. Project the environmental effectiveness of GAEC cross-compliance Standard 3.1 Ploughing in good soil moisture conditions was evaluated, as well as the economic evaluation of the competitiveness gap for farmers which conform or do not conform to cross-compliance. The monitoring has been carried out at nine experimental farms with different pedoclimatic characteristics, where some indicators of soil structure degradation have been evaluated, such as bulk density, packing density and surface roughness of the seedbed, and the crop productive and qualitative parameters. In each monitoring farm two experimental plots have been set up: factual with soil tillage at proper water content (tilth), counterfactual with soil tillage at inadequate water content (no tilth). The monitoring did not exhibit univocal results for the different parameters, thus the effectiveness of the Standard 3.1 is contrasting (class of merit B), and there was an evident practical problem to till the soil at optimum water content, even in controlled experimental condition. Bulk density was significantly lower in the factual treatment although in soils with very different textures (sandy-loam and clayey). Packing density (PD) showed a high susceptibility to compaction in soils with low PD and medium texture. The tortuosity index, indicating the roughness of the seedbed, was lower and generally significantly different in the factual treatment. Results showed that the ploughing done in excessive soil moisture conditions is more expensive due to the increased force of traction of the tractor, which causes an increase in slip of the tractor wheels, with a speed reduction and increase in the working times and fuel consumption. Moreover, the crop yield is also reduced considerably according to the cultivated species.